The Growth Of White Oyster Mushroom Mycelium (Pleurotus ostreatus) (Jacq) (P. Kumm) From Liquid And Solid Inoculum - Nisfaun Safitriana; Umrah; Orryani Lambui (Biology Department, Mathematics and natural science, Tadulako University, 2019)
The study about the growth of white oyster mushroom mycelium (Pleurotus ostreatus) (Jacq) (P. Kumm) from liquid and solid inoculum conducted on January until July 2018 in Biotechnology laboratory, Biology Department, Faculty of Math and Science, Tadulako University. This study was aimed to find out the mycelium growth of source of stem inoculum and hood in liquid and solid media. This study was designed by Complete Randomized Design (CRD) which consisted of four treatments and five replications. The treatment were M1 (source of stem inoculum in liquid medium), M2 (source of stem inoculum in solid medium), M3 (source of hood inoculum in liquid medium), and M4 (source of hood inoculum in solid medium). The parameters were (a) incubation time till mycelium fills medium, (b) CFU, and (c) the viability of inoculum on producing medium. The result showed that the faster incubation were M1 and M3 (for 2 days, higher CFU was M3 with an average number 8,2 x 10 10 CFU /ml. The faster viability of mycelium growth were M3 with an average growth of mycelium 6,97 cm/days.